Karyotypic studies in Lycium section Mesocope (Solanaceae) from South America - Stiefkens, Laura Beatriz (2002)
Mitotic chromosome numbers and karyotypes were determined for South American species of Lycium L. section Mesocope Miers (Tribe Lycieae). Twenty populations from nine species were examined. All of them have 2n = 2x = 24, a fact that confirms the basic number x = 12 suggested for the tribe and the subfamily Solanoideae. The chromosome numbers of L. chanar, L. minutifolium, L. stenophyllum, and L. vimineum are reported for the first time and data on karyotype composition are all new. Chromosome measurements were statistically compared and a phenogram was obtained with those data. Results suggest that although these species are morphologically different, their differentiation was not followed by variations in chromosome number or structure. The karyotype of all the studied taxa is composed of 11 m pairs + 1 sm pair (pair #1 bears a microsatellite on the short arm) showing slight differences in size among the species. Thus, during the diversification within the section, no major visible chromosomal rearrangements have occurred, although cryptic structural changes, as paracentric inversions or reciprocal translocations of segments of similar length may have taken place. © 2002 Taylor & Francis Group, LLC.